2012
DOI: 10.1111/tpj.12050
|View full text |Cite
|
Sign up to set email alerts
|

The tyrosine‐sulfated peptide receptors PSKR1 and PSY1R modify the immunity of Arabidopsis to biotrophic and necrotrophic pathogens in an antagonistic manner

Abstract: SUMMARYThe tyrosine-sulfated peptides PSKa and PSY1 bind to specific leucine-rich repeat surface receptor kinases and control cell proliferation in plants. In a reverse genetic screen, we identified the phytosulfokine (PSK) receptor PSKR1 as an important component of plant defense. Multiple independent loss-of-function mutants in PSKR1 are more resistant to biotrophic bacteria, show enhanced pathogen-associated molecular pattern responses and less lesion formation after infection with the bacterial pathogen Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
168
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 165 publications
(186 citation statements)
references
References 75 publications
(131 reference statements)
8
168
0
1
Order By: Relevance
“…CNGCs may thus be general targets of LRR-RLKs that possess GC activity. Recent studies showed that PSK not only regulates growth but also modulates immune responses through PSKR1 (Igarashi et al, 2012;Mosher et al, 2013). It is tempting to speculate that CNGC17 may not only play a role in growth regulation but also in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…CNGCs may thus be general targets of LRR-RLKs that possess GC activity. Recent studies showed that PSK not only regulates growth but also modulates immune responses through PSKR1 (Igarashi et al, 2012;Mosher et al, 2013). It is tempting to speculate that CNGC17 may not only play a role in growth regulation but also in immunity.…”
Section: Discussionmentioning
confidence: 99%
“…by Mosher et al (2012). Alternaria brassicicola infection assays were carried out as 521 described by Kemmerling et al (2007).…”
Section: Infection Procedures 519mentioning
confidence: 99%
“…Transcript levels were analyzed by standard or quantitative RT-PCR (qRT-PCR) 543 using SYBR-green as a dye as described by Mosher et al (2012) with primers listed 544 in Supplemental Table 2. 545 546…”
Section: Rt-pcr Analysis 542mentioning
confidence: 99%
“…Similar to fer mutants, Arabidopsis mutants lacking PSKR1 or TYROSINE PROTEIN SULFOTRANSFERASE (TPSP), the latter of which is required for sulfation of PSKs, exhibit enhanced defense gene expression in response to elf18 and flg22 and increased disease resistance to P. syringae, indicating a negative role of PSKR1 in pattern-triggered immunity (Igarashi et al, 2012). Similarly, PSKR1 and PSY1R play an additive role in the negative regulation of disease resistance to the fungal pathogen Alternaria brassicicola in addition to P. syringae (Mosher et al, 2013). The pskr1 pskr2 psy1r triple mutant is strongly enhanced in flg22-induced defense gene expression.…”
Section: Crosstalk Between Rlk-mediated Immune Signaling and Growth/dmentioning
confidence: 99%